2005
DOI: 10.1111/j.1365-2958.2005.04673.x
|View full text |Cite
|
Sign up to set email alerts
|

The ClpX chaperone modulates assembly of the tubulin‐like protein FtsZ

Abstract: SummaryAssembly of the tubulin-like cytoskeletal protein FtsZ into a ring structure establishes the location of the nascent division site in prokaryotes. Factors that modulate FtsZ assembly are essential for ensuring the precise spatial and temporal regulation of cytokinesis. We have identified ClpX, the substrate recognition subunit of the ClpXP protease, as an inhibitor of FtsZ assembly in Bacillus subtilis . Genetic data indicate that ClpX but not ClpP inhibits FtsZ-ring formation in vivo . In vitro , ClpX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
96
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 55 publications
7
96
2
Order By: Relevance
“…Based on these results, they proposed that ClpXP may participate in cell division by modulating the equilibrium between monomeric and polymeric FtsZ via degradation of FtsZ polymers. In contrast, it has been reported that in B. subtilis ClpXP does not degrade FtsZ and that ClpX regulates FtsZ polymer dynamics by preventing FtsZ polymerization (19). Our present results mentioned above are consistent with the latter result, but contribution of FtsZ degradation (or unfolding) by ClpXP (or ClpX) to the regulation of FtsZ polymer dynamics remains to be elucidated.…”
Section: Clpx Recognizes a C-terminal Moiety And Other Parts Of Ftsz-supporting
confidence: 66%
See 1 more Smart Citation
“…Based on these results, they proposed that ClpXP may participate in cell division by modulating the equilibrium between monomeric and polymeric FtsZ via degradation of FtsZ polymers. In contrast, it has been reported that in B. subtilis ClpXP does not degrade FtsZ and that ClpX regulates FtsZ polymer dynamics by preventing FtsZ polymerization (19). Our present results mentioned above are consistent with the latter result, but contribution of FtsZ degradation (or unfolding) by ClpXP (or ClpX) to the regulation of FtsZ polymer dynamics remains to be elucidated.…”
Section: Clpx Recognizes a C-terminal Moiety And Other Parts Of Ftsz-supporting
confidence: 66%
“…Recently, it has been reported that in Bacillus subtilis ClpX inhibits FtsZ polymerization in vivo and in vitro in an ATP-independent manner but does not degrade it (19,20). However, molecular mechanisms of regulating FtsZ monomerpolymer dynamics are still largely unknown.…”
mentioning
confidence: 99%
“…As ZipA and EzrA bind directly to FtsZ, they must therefore regulate FtsZ assembly at the membrane. Recently, the conserved chaperone ClpX was also found to inhibit Z-ring formation in B. subtilis 76 . Purified ClpX can inhibit FtsZ polymerization, although GTP hydrolysis is not affected, indicating that ClpX functions after the initial assembly of protofilaments.…”
Section: Other Regulators Of Z-ring Assemblymentioning
confidence: 99%
“…MciZ is a 40-amino-acid (aa) peptide involved in the inhibition of FtsZ ring assembly following sporulation in B. subtilis (29). ClpX, a part of the ClpXP protease complex, inhibits FtsZ polymerization and possibly helps to maintain cytoplasmic pools of unpolymerized FtsZ subunits (5,20,25,44,50). Finally, the Min system spatially regulates cell division by preventing FtsZ assembly at the cell poles (27).…”
mentioning
confidence: 99%